Trauma, PTSD, and Self-Efficacy: Predictors of Cervical Cancer Screening in Sexual Violence Survivors - Bengtson, Lillian (Journal of interpersonal violence, 2025)
Sexual violence is highly prevalent in the United States and is associated with a host of negative physical and mental health outcomes. Specifically, sexual violence is associated with increased rates of cervical cancer, one of the most common cancers found in women. Furthermore, sexual violence survivors report reduced participation in preventive healthcare behaviors (e.g., Pap tests) which may reduce individuals’ risk of developing reproductive health conditions such as cancer. Sexual violence exposure is also associated with increased symptoms of posttraumatic stress disorder (PTSD) and reduced trauma-coping self-efficacy (TCSE), two factors that may impact trauma-exposed individuals’ level of avoidance of cervical cancer screens. Current research on the connection between sexual violence and reproductive healthcare often fails to examine potential underlying mechanisms behind this association, nor does it account for confounding factors such as healthcare accessibility and need. Accordingly, the present study tested a proposed moderated mediation model to explore the association between sexual violence and cervical cancer screening participation, including analysis of the indirect effect of TCSE and potential moderation of this effect by PTSD symptoms. Participants were 554 participants who reported experiences of sexual violence on Amazon’s Mechanical Turk. Severity of sexual violence was significantly associated with reduced likelihood of participation in recommended cervical cancer screening. TCSE did not mediate nor did PTSD moderate this association. Findings of this study suggest that individuals’ reproductive healthcare behaviors are influenced by their experiences of sexual trauma, as well as by structural factors such as insurance and income. Limitations, directions for future research, and clinical implications of study findings are discussed.